Exteriorization of uterus versus intrabdominal uterine closure at Caesarean delivery - Lamichhane, Basant; Pokharel, Shreesiya (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To assess the intraoperative and post-operative complications of exteriorization repair with intrabdominal repair of uterus during caesarean delivery. Method: This was a prospective comparative study of 150 caesarean deliveries. Randomization of the cases was irrespective of age, parity, indication and elective or emergency and was performed by two surgeons. Total of 150 cases were considered in the study and 75 cases performed by each surgeon were selected. One surgeon performed the surgery as intrabdominal repair while the other exteriorized the uterus for closure. Descriptive parameter and t-test were used. Results: Intraoperative complications like intraoperative nausea, vomiting, pain were more commonly associated in cases in which uterus was exteriorized. In regards to severity of blood loss in either group there was no significant difference in either group (1.28±1.00, 1.23±0.98). The study revealed no significant difference in febrile morbidity and wound infections in either group. Conclusions: There is no significant difference in the post-operative morbidity between the two groups but intraoperative peritoneal stretching pain was more when uterus was exteriorized. Keywords: caesarean delivery, exteriorization, intrabdominal repair, uterine closure